Dried human-cultured epidermis accelerates wound healing in a porcine partial-thickness skin defect model - Takashi Nakano; Michiharu Sakamoto; Yasuhiro Katayama; Yoshihiro Shimizu; Masukazu Inoie; Yuanjiaozi Li; Hiroki Yamanaka; Itaru Tsuge; Susumu Saito; Naoki Morimoto (Regenerative Therapy, 2023)
Introduction: Autologous cultured epidermis (CE) is an effective approach for overcoming the deficiency of donor sites to treat extensive burns. However, the production of autologous CE takes 3–4 weeks, which prevents its use during the life-threatening period of severe burns. In contrast, allogeneic CE can be prepared in advance and used as a wound dressing, releasing several growth factors stimulating the activity of recipient cells at the application site. Dried CE is prepared by drying CEs under controlled temperature and humidity conditions until all the water is completely removed and no viable cells are present. Dried CE accelerates wound healing in a murine skin defect model and is potentially a new therapeutic strategy. However, the dried CE safety and efficacy have not yet been studied in large animal models. Therefore, we studied the safety and efficacy of human-dried CE in wound healing using a miniature swine model. Methods: Human CE was manufactured using Green's method from donor keratinocytes. Three types of CEs (Fresh, Cryopreserved, and Dried) were prepared, and the ability of each CE to promote keratinocyte proliferation was confirmed in vitro. Extracts of the three CEs were added to keratinocytes seeded in 12-well plates, and cell proliferation was evaluated using the WST-8 assay for 7 days. Next, we prepared a partial-thickness skin defect on the back of a miniature swine and applied three types of human CE to evaluate wound healing promotion. On days 4 and 7, the specimens were harvested for hematoxylin-eosin, AZAN, and anti-CD31 staining to assess epithelialization, granulation tissue, and capillary formation. Results: The conditioned medium containing dried CE extract significantly enhanced keratinocyte proliferation compared to the control group (P < 0.05). In vivo experiments revealed that human-dried CE significantly accelerated epithelialization at day 7 to the same extent as fresh CE, compared to the control group (P < 0.05). The three CE groups similarly affected granulation formation and neovascularization. Conclusions: Dried CE accelerated epithelialization in a porcine partial-thickness skin defect model, suggesting that it may be an effective burn treatment alternative. A clinical study with a long-term follow-up is needed to assess the applicability of CEs in clinics.